Effectiveness of psychosocial interventions in reducing grief experienced by family carers of people with dementia: a systematic review protocol. - Wilson, Sally; Toye, Christine; Aoun, Samar; Slatyer, Susan; Moyle, W.; Beattie, E. (Joanna Briggs Institute, 2016)
REVIEW OBJECTIVE: The objective is to examine the existing evidence regarding the effectiveness of psychosocial interventions to assist grief pre- and post-bereavement for family carers of people with dementia residing in the community or in a health or social care facility. REVIEW QUESTION: What psychosocial interventions for family carers of people with dementia are most effective in reducing: (1) anticipatory grief, (2) post-death grief (bereavement), and (3) complicated grief?